Tourists’ Behavior and Expectations in Wellness Tourism: A Study of Phuket, Thailand - Chaopreecha, Jakraphan; Tovankasame, Nicha; Wae-Esor, Emeela (Journal of International Studies, Prince of Songkla University, 2024)
The objective of this research was to study behavior and expectations of Thai and foreign tourists in order to understand market demand and market potential of wellness tourism in Phuket, Thailand. The sample size was 434 Thai and foreign tourists. Convenience Sampling was used as a sampling technique in this study. The results of the study showed that destination quality, namely beach attractions, was the main factor influencing tourists’ choice of destination (23.92%). Most of the respondents were interested in experiencing food-related activities (28.10%). It was also found that the respondents had expectations, which created motivation for them to take into account the most nature-friendly and healthy for products and services. They also placed importance on destinations with good weather (x̄ = 4.43), followed by the desire to experience natural aesthetics (x̄ = 4.39).